2021
DOI: 10.24246/jrh.2021.v6.i1.p87-106
|View full text |Cite
|
Sign up to set email alerts
|

Eksistensi Adat Dalam Keteraturan Sosial Etnis Dayak Di Kampung Bonsor Binua Sakanis Dae

Abstract: Abstrak Masyarakat Dayak di Kampung Bonsor Binua Sakanis Dae, hingga kini menggunakan adat sebagai instrumen penyelesaian sengketa ataupun persoalan sosial budaya ini bertujuan untuk mengungkapkan eksistensi adat dalam keteraturan sosial masyarakat Dayak di Kampung Bonsor Binua Sakanis Dae. Penelitian ini menggunakan pendekatan etnografis yang dilakukan dengan wawancara secara mendalam, observasi partisipatif dan juga pendokumentasian data dan informasi. Penelitian ini menunjukkan bahwa eksistensi adat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In general, the Dayak indigenous peoples operate on the basis of customary norms and traditions prevailing in their area (Anggerainy, Wanda, & Hayati, 2017; Boulanger, 2002; Gerke, 1997; Nugraha & Hasanah, 2021). Psychologically, they are bound by the culture they adhere to as a law they have to obey, so that all forms of behaviour and character of indigenous peoples must be in accordance with the culture they believe in (Efriani et al, 2021; Efriani, Dewantara, et al, 2020; Taufika, Simaremare, Chairunnisa, & Nadhira, 2021). For indigenous peoples who live and settle in areas under customary law, such as the Salako Dayak on the border of West Kalimantan, their response to the pandemic is manifested by closing or limiting entry to their areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, the Dayak indigenous peoples operate on the basis of customary norms and traditions prevailing in their area (Anggerainy, Wanda, & Hayati, 2017; Boulanger, 2002; Gerke, 1997; Nugraha & Hasanah, 2021). Psychologically, they are bound by the culture they adhere to as a law they have to obey, so that all forms of behaviour and character of indigenous peoples must be in accordance with the culture they believe in (Efriani et al, 2021; Efriani, Dewantara, et al, 2020; Taufika, Simaremare, Chairunnisa, & Nadhira, 2021). For indigenous peoples who live and settle in areas under customary law, such as the Salako Dayak on the border of West Kalimantan, their response to the pandemic is manifested by closing or limiting entry to their areas.…”
Section: Discussionmentioning
confidence: 99%
“…Customs are used as a source of norms that regulate people's lives in social life, culture, conflict management, and their way of life (Dewantara, Darmawan, Hijjang, & Tamambaloh, 2020;Efriani et al, 2021;Jailani, Dewantara, & Rahmani, 2021). Therefore, the Dayak ethnic cultural orientation has a value orientation related to social and religious life (Sada et al, 2019), while Efriani et al (2021) explain that religious belief is observed through customs and customary law (Efriani et al, 2021). The Dayak people believe that there is a belief in the existence of a higher power beyond human ability, namely the power of Jubata.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The community has an agreement to go to a place called Darakng and that's where the community performs traditional ceremonies with the aim of asking for protection to avoid the plague. According to (Efriani et al, 2021) traditions tend to exist because the community has experience and life practices, so they regard this as an order of social harmony that is formed into customary law. Harmony means compatible and in li1ne (Saiful et al, 2022).…”
Section: Balala' Tamakng Traditionmentioning
confidence: 99%